Implementation of E-Government in South Jakarta: A Case Study of Digital Services Through The Digital Application of Polri's Traffic Corps - Mohammad Rizki Adhari Jusal (Green Publisher Indonesia, 2024)
This research examines the implementation of e-government through the Digital Application of the Indonesian National Police Traffic Corps (Korlantas POLRI) in South Jakarta in an effort to improve the quality of public services, particularly in the processing of driving license (Surat Izin Mengemudi or SIM) renewals. This application aims to facilitate the public in renewing SIM cards online without having to visit the SATPAS office. The implementation of this application has provided positive impacts in terms of service efficiency and effectiveness, ease of access, and increased public satisfaction. However, there are challenges such as digital divide and concerns about the security of personal data. Factors influencing the success of implementation include effective communication, smooth and efficient implementation activities, and the disposition or attitude of policy implementers. There are inputs and criticisms from the public regarding the payment system, the length of the renewal process at some SATPAS offices, lack of clear information, and requests to move or cancel applications. Improvement efforts are needed in terms of the payment and online registration systems, increasing the capacity of SATPAS offices, information transparency, and flexibility for users in choosing SATPAS offices. The implementation of this application provides benefits in improving the quality of public services, but there are still challenges that need to be overcome to optimize success and increase public satisfaction.